HLA gene polymorphism among Bangladeshi patients with end-stage renal disease awaiting kidney transplantation (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Proper matching of HLA class I and class II antigens among donor and recipient is an important prerequisite for the long survival of a transplanted organ. To reveal the HLA gene polymorphism among end-stage renal disease (ESRD) patients and their donors, a total of 180 ESRD patients and 320 donors, referred by clinicians for HLA typing, were included in this study. HLA typing was performed using Polymerase Chain Reaction-Se- quence Specific Primer (PCR-SSP). The most frequent alleles reported from both groups were, A*11, A*02 and A*33 in A locus; B*15:02, B*35 and B*52 in B locus and DRB1*15, DRB1*07 and DRB1*04 in DR locus. Frequencies of four alleles, A*26, B*57, B*40 and DRB1*11 were found to be higher in ESRD patients. The three locus haplotypes A*24, B*15:02, DRB1*15 were observed more frequently among recipients than in donors. The results were found to be in genetic equilibrium. Higher frequencies of certain alleles in recipients may be indicative of risk factor for renal disease. Further studies are needed to corroborate the findings of this study.BSMMU J 2022; 15(1): 01-10